2020
DOI: 10.1186/s40834-020-00132-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual and community-level factors associated with modern contraceptive use among adolescent girls and young women in Mali: a mixed effects multilevel analysis of the 2018 Mali demographic and health survey

Abstract: Background Unintended pregnancy constitutes a significant public health challenge in sub-Saharan Africa and particularly among young people, who are more likely to closely space births and experience adverse obstetric outcomes. Studies on modern contraceptive use have mostly focused on women of reproductive age in general with limited attention to factors associated with modern contraceptive use among adolescents and young women (aged 15–24) in Mali. We examined the individual and community-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 34 publications
(58 reference statements)
11
39
1
Order By: Relevance
“…Our study also revealed that married AGYW had a better tendency to use modern contraceptive methods. The result was comparable with the studies in Ethiopia [ 33 ], Ghana [ 34 ], and in conflict with the study done in Mali [ 35 ]. The possible explanation might be the exposure to maternal and birth control services during antennal and postnatal cares.…”
Section: Discussionsupporting
confidence: 87%
“…Our study also revealed that married AGYW had a better tendency to use modern contraceptive methods. The result was comparable with the studies in Ethiopia [ 33 ], Ghana [ 34 ], and in conflict with the study done in Mali [ 35 ]. The possible explanation might be the exposure to maternal and birth control services during antennal and postnatal cares.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with previous studies (Ahinkorah et al, 2020;Nsanya et al, 2019), we also observed that reproductive aged women in PNG with no information on choice were more likely to discontinue contraceptive use compared to their counterparts who had information. Timely and accurate information is key with regards to contraceptive uptake.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the numerous policy interventions aimed at preventing adolescent childbearing in many countries across the world, the prevalence of adolescent pregnancy and childbirth remains high [ 1 – 3 ]. Adolescent childbearing has been defined as birth that occurs among adolescents aged 10-19 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%